Albumin-mediated "Unlocking" of supramolecular prodrug-like nanozymes toward selective imaging-guided phototherapy. Issue 26 (16th June 2022) - Han, Jingjing; Li, Haidong; Zhao, Luyang; Kim, Gyoungmi; Chen, Yahui; Yan, Xuehai; Yoon, Juyoung
Abstract : An adaptive nanozyme without producing off-target toxicity has been successfully applied in phototherapy. Abstract : Construction of an activatable photosensitizer and integration into an adaptive nanozyme during phototherapy without producing off-target toxicity remains a challenge. Herein, we have fabricated a prodrug-like supramolecular nanozyme based on a metallic-curcumin and cyanine co-assembly. The albumin-mediated phenol AOH group transformation of nanozyme changes its adjustable oxygen stress from negative superoxide dismutase-like activity of ROS-scavenging to positive photo oxidase activity with an ROS-amplifying capacity. It further increases the depth penetration of a nanozyme in a tumor spheroid, selectively targeting tumorous phototherapy. It also triggers a signal in targeted tumor cells and helps increase cancer cell ablation. This work suggests new options for development of activatable supramolecular nanozymes and provides a synergetic prodrug-like nanozyme strategy for early diagnosis and preclinical phototherapeutics.